Transformasi Pembelajaran Bahasa: Analisis Penerimaan “Duolingo” Menggunakan Model TAM pada Program GWEP - Setiyani, Lila; Dedih, Dedih; Fajar Wati, Devi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research was conducted at Horizon University of Indonesia in order to implement the Global Workplaces English Program (GWEP), which encourages the development of students' foreign language skills through technology integration. Duolingo, as one of the digital language learning applications, is widely used by students to support this programme. The purpose of this study is to analyse the level of user acceptance of Duolingo using the Technology Acceptance Model (TAM), which involves the constructs of Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Use (ATU), and Behavioral Intention to Use (BIU). Data were collected through a survey of 152 active Duolingo users, and analysed using descriptive statistics and multiple linear regression approaches. Descriptive results showed that all constructs had an average score above 4 (Likert scale 1-5), reflecting positive perceptions of the ease of use and usefulness of the app. Linear regression analysis showed that PEOU and PU had a significant effect on ATU, with coefficients of 0.508 and 0.447, respectively, and R² = 0.857. That is, 85.7% of the variation in user attitudes can be explained by perceived ease and usefulness. These findings provide strategic implications for educational institutions and application developers in optimising the use of digital technology for foreign language learning in the global era.